A review of therapeutic agents for the management of pulmonary arterial hypertension - Stella S Hahn (Therapeutic Advances in Respiratory Disease, 2017)
Pulmonary arterial hypertension (PAH) is an uncommon, progressive and life threatening disease characterized by a proliferative vasculopathy of the small muscular pulmonary arterioles resulting in elevated pulmonary vascular resistance and eventually right ventricular failure. An increasing understanding of the pathobiology of PAH and its natural history has led to the development of numerous targeted therapies. Despite these advances there is significant progression of disease and the survival rate remains low. This article reviews the agents currently available for the medical management of PAH.